Higgs Domino Island” Game Addiction Among Teenagers In Surabaya - Putra, Surya Jaya Purnama; Suryanto, Suryanto; Meiyuntariningsih, Tatik (Yayasan Minang Darussalam, 2022)
The aims of this study were: 1.) to identified forms of addiction, 2.) intensity of addiction, and 3.) factors of games which are sources of addiction. This research uses qualitative and the method used is the case study method. The subjects of this study were teenagers who played the game